Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI di SMP Muhammadiyah 07 Blimbing - Rohmah, Zahrotur (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
There is a problem with learning Islamic Religious Education (PAI) which is considered monotonous, making students bored and not interested in studying PAI subjects, even if students are forced, the results will not be optimal. For this reason, a new formulation is needed, which in this case tries to apply a snowball throwing type cooperative learning model to improve student learning outcomes. This research was aimed at finding out the snowball throwing type cooperative learning model at Muhammadiyah 07 Blimbing Middle School as well as knowing the influence of the snowball throwing type cooperative learning model on the learning outcomes of PAI subjects at Muhammadiyah 07 Blimbing Middle School. The snowball throwing type cooperative learning model is where the teacher divides the students into several groups, then after the teacher explains the material each group is given time to study the material again, the teacher prepares questions on sheets of paper then the paper is shaped like a snowball, then thrown to one of the students and the students The person who gets the question thrown is obliged to answer the question.